Evaluating the emission of VOCs and HCHO from furniture based on the surface finish methods and retention periods - Sherzad, Mohammed; Jung, Chuloh (Frontiers in Built Environment, 2022)
Furniture emits various VOCs and formaldehyde (CH2O) into the indoor air. These indoor air pollutants can cause SBS (Sick Building Syndrome), such as sickness, headache, dizziness, nausea, drowsiness, and loss of concentration. This paper aims to provide essential data for improving indoor air quality by identifying the characteristics of the emission of VOCs and CH2O according to the characteristics of raw materials and finishing methods for furniture materials. As a meth-odology, a small chamber experiment was conducted witeight 8 different test pieces, which have different compositions of base materials and surface finishing methods. VOCs and CH2O were collected and analyzed by GC/MS (Gas Chromatography/Mass Spectrometry) and HPLC (High-Performance Liquid Chromatography). The result showed that the TVOC in the composite material differed according to the retention period of the raw material. CH2O is preferentially affected between the processing method and the storage period after molding rather than the retention period of raw materials. TVOC emission was lower when the surface finishing method was applied, like paint finish. CH2O emission was getting lower when the adhesive was used during molding. Furniture applied to new houses is installed indoors in the form of finished products (composite materials). It was confirmed that the emission amount from furniture was generally higher than that of the general interior finishing material. Not only using eco-friendly raw materials, securing a specific retention period for raw materials, selecting eco-friendly pro-cessing methods, securing a particular retention period after molding, and post-construction management (ventilation and bake-out) should be done through a comprehensive evaluation of furniture.